2016
DOI: 10.1111/ijet.12087
|View full text |Cite
|
Sign up to set email alerts
|

Arms build‐up and arms race in optimal economic growth

Abstract: I analyze a model of strategic interdependence between two economies linked by investments in defensive capital for deterrence purposes. I adapt a two‐agent dynamic setting where weapon production affects consumption. Individually both economies determine their balanced growth path by taking this interdependence into account in different grades of awareness. I associate two types of equilibria with internal or external determinants for defense production analogous to scenarios of arms build‐up or arms race. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Ayrıca, yüksek düzeydeki savunma harcamaları savunma sanayinde, diğer sektörlere yayılma potansiyeline sahip yeni bilgi ve teknolojilerin geliştirilmesini sağlamıştır. Daha sonra yapılan Ball (1983), Lipow and Antinori (1995), Akal et al, (2011), Dunne and Nikolaidou (2012), Ali and Ather (2015), Elveren (2016), Larrosa (2016), Töngür and Elveren (2017) gibi uygulamalı çalışmalarda savunma harcamalarının büyüme üzerindeki olumsuz etkilerine yönelik bulgular elde edilmiştir. Bu çalışmalar, askeri harcamalardaki artışın toplumsal ihtiyaçlar, eğitim, altyapı, sağlık gibi alanlara yönelik kaynakları azalttığını ve diğer sektörlerdeki özel yatırımları baskıladığını öne sürmektedir.…”
Section: Li̇teratür İncelemesi̇unclassified
“…Ayrıca, yüksek düzeydeki savunma harcamaları savunma sanayinde, diğer sektörlere yayılma potansiyeline sahip yeni bilgi ve teknolojilerin geliştirilmesini sağlamıştır. Daha sonra yapılan Ball (1983), Lipow and Antinori (1995), Akal et al, (2011), Dunne and Nikolaidou (2012), Ali and Ather (2015), Elveren (2016), Larrosa (2016), Töngür and Elveren (2017) gibi uygulamalı çalışmalarda savunma harcamalarının büyüme üzerindeki olumsuz etkilerine yönelik bulgular elde edilmiştir. Bu çalışmalar, askeri harcamalardaki artışın toplumsal ihtiyaçlar, eğitim, altyapı, sağlık gibi alanlara yönelik kaynakları azalttığını ve diğer sektörlerdeki özel yatırımları baskıladığını öne sürmektedir.…”
Section: Li̇teratür İncelemesi̇unclassified
“…Later on, empirical studies of Ball (1983), Landau (1996), Lipow and Antinori (1995), Heo (1998), Dunne and Nikolaidou (2012), Dunne and Tian (2015), Töngür and Elveren (2017), Elveren (2016), Ali and Ather (2015), Paparas et al (2016) and Larrosa (2016) showed a negative relationship between the military expenditures and growth. These studies described military expansion as a financial burden on the country's resources.…”
Section: Introductionmentioning
confidence: 99%